Peering Inside the Preliminary Reference Box: Coleman v Attridge Law - Jeffrey A. Miller (European Papers, 2022)
(Series Information) European Papers - A Journal on Law and Integration, 2021 6(3), 1553-1574 | Article | (Table of Contents) I. Introduction. - II. Passalacqua's theory of EU legal mobilization. - III. The Coleman v Attridge litigation. - III.1. Altruism. - III.2. Euro-expertise. - III.3. An open EU legal opportunity structure. - IV. Coleman contributes to a new interpretation of national law. - V. EU legal mobilization in theory and practice | (Abstract) The importance of the preliminary reference procedure for the production of EU case-law is widely recognized in EU legal scholarship, but uncovering the motivations and strategies of the individuals that are involved in the preliminary reference procedure is difficult. The conditions that have the potential to influence whether a national judge poses a preliminary reference to the Court of Justice are so varied and complex that generalizations are difficult to discern. In a recent article, Virginia Passalacqua argues that preliminary reference legal mobilization is most likely to occur when three conditions exist: altruism, Euro-expertise, and a favourable EU legal opportunity structure. This Article tests Passalacqua's theory by applying it to a new area of law. Although Passalacqua derived her theory from an intimate knowledge of EU migration law, her theory "travels well" when it is extended to a new domain, namely, EU disability rights litigation.